SUGGESTIONS FOR THE REVISION OF THE TENTATIVE STATEMENT OF ACCOUNTING PRINCIPLES. - Littleton, A. C. (The Accounting Review, 1939)
In June 1936, the executive committee of the American Accounting Association published "A Tentative Statement of Accounting Principles." Accounting theory has been debated in the Association's annual meetings and in accounting periodicals with an energy never before displayed. From the beginning the Committee recognized the tentative nature of the statement of principles and looked forward to the time when revision would be undertaken. The appearance of revenue marks the accomplishment of the principal objective of business, namely, placing new utilities in the hands of consumers. The tests by which the reality of the profit or loss that may be embedded in revenue has been judged are as follows, economic tests, service has been rendered by a producer, utility has been accepted by a purchaser, a price has been determined by independent bargaining; legal tests, delivery has been completed, title to product has been passed, producer's claim for payment in due course is "property." Since the association of revenue and performance is basic to the concept of revenue, accounting standards should direct the preservation of that association; recognition of revenue should neither anticipate performance nor be delayed beyond performance.